AB0557 CO-EXISTENCE OF SYSTEMIC SCLEROSIS HALLMARK AUTOANTIBODIES ASSOCIATES WITH DISTINCT CLINICAL PHENOTYPE. (2nd June 2020) - Campochiaro, C.; Clark, K.; Host, L.; Sari, A.; Nihtyanova, S.; Denton, C.; Ong, V.
Abstract : Background: Systemic sclerosis (SSc) is typically manifests with distinct SSc-specific antibodies (SSc-Abs): anti-topoisomerase I (ATA), anti-centromere (ACA), anti-RNA polymerase III (ARA), anti-U3RNP (u3RNP), anti-U1RNP (U1RNP), anti-PmScl (PmScl), anti-Ku (Ku) and anti-Th/T0 (Th/T0), each being characterised by different clinical features and prognosis. The presence of >1 SSc-Abs is rare with minimum data about these patients' clinical phenotype. Objectives: To describe and compare the clinical features of SSc patients with >1 SSc-Ab Methods: The autoantibody profiles of 2799 SSc patients from February 2001 to June 2017 were retrospectively reviewed. Patients with >1 SSc-Abs were identified. Clinical features were collected and compared to historical cohorts of SSc patients with single SSc-Ab positivity. Patients were excluded if treated prior to their immunology test with rituximab, iv immunoglobulins or stem cell transplantation. Statistical analysis was performed using Fisher exact test. Results: 72 patients (2.6%) with >1 SSc-Ab were identified. Full clinical data were available for 63 patients. 60 patients (2.1%) had double Ab positivity and 3 patients had triple Ab positivity (0.1%). 13 Ab combinations were present. U1RNP and ATA was the most frequent combination (35%), patients were significantly younger (51.38 years) than both U1RNP (58.64 years, p=0.050) and ATA (62.03 years, p=0.002) patients and more commonly of diffuse subset (dcSSc) (p=0.001 and p=0.041 respectively). Compared to ATA patients overlap features were more frequent (43% vs 15%, p=0.004) including inflammatory arthritis (p=0.025) and myositis (p=0.013) (Table 1 ). U1RNP and ACA had a significantly higher prevalence of pulmonary arterial hypertension compared to U1RNP (p=0.039) and ACA (p=0.022) patients, and compared to ACA patients they were younger (57.88 vs 68.75, p=0.015) with a higher incidence of myositis (p=0.001). U1RNP and ARA patients were more frequently dcSSc subtype compared to U1RNP patients (75% vs 21%, p=0.040). U1RNP and PmScl patients had a higher prevalence of myositis compared to U1RNP patients (p=0.006). ATA and ACA patients behaved similarly to ATA patients with a significantly higher prevalence of lung fibrosis (p=0.006) and myositis (p=0.041) compared to ACA. ACA and PmScl (7%) had higher prevalence of myositis compared to ACA patients (p=0.04). Table 1. Frequency of clinical features in some of the double antibody group combinations, compared to our cohort of patients with only one of the SSc specific antibody. Significant p values (<0.05) highlighted in bold. ILD (interstitial lung disease), PAH (pulmonary arterial hypertension), SRC (scleroderma renal crisis). Conclusion: Coexistence of hallmark autoantibodies is exceedingly rare in SSc patients. When combined, both SSc-Abs have the potential to synergistically interact and modify the clinical phenotype. Disclosure of Interests: Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Kristina Clark: None declared, Lauren Host: None declared, Alper Sari: None declared, Svetlana Nihtyanova: None declared, Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer, Voon Ong: None declared